Elections with Integrity: Initiating the Revocation of Political Rights for Corruption Inmates Selected through General Elections - Saleh, Muhamad; Hunafa, Dimas Firdausy (Law Research Review Quarterly, 2018)
For democracies, the implementation of general elections (elections) is a necessity. Article 22E Paragraph (1) of the 1945 Constitution says "General elections shall be held directly, publicly, freely, confidentially, honestly and fairly once every five years". The meaning of honesty in this context is binding for 3 (three) parties, namely the election organizer who will oversee the election from the stages of preparation, implementation and settlement, election participants (political parties and prospective participants) and the public as holders of voting rights. Election integrity has become very problematic at least from the many corruption cases involving election administrators. This can be a real visualization of the election integrity crisis in Indonesia. The crisis of integrity is increasingly apparent when corrupt convicts are still given the opportunity to run in the election. The problem in this research is First, what is the urgency of revoking political rights for prisoners of corruption. Second, how the ideas offered to regulate the revocation of political rights for prisoners of corruption. This research is a doctrinal research that uses primary and secondary legal materials. The method used is the normative approach. The results of the study concluded that first public office must be filled by people who are clean of corruption. Second, the application of revocation of political rights as a deterrent effect. Third, the need for a revision of the Anti-Corruption Law and the Election Law. Fifth, the granting of qualifications against convicted of criminal acts of corruption whose political rights will be revoked.